HIV-Related Non-Hodgkin's Lymphoma in Calgary. (1996) - Beck, Paul L; Gill, M John; Blahey, Walter B; Sutherland, Lloyd R
Abstract : OBJECTIVE: To determine the incidence of human immunodeficiency virus (HIV) associated non-Hodgkin's lymphoma (NHL) in a cohort of patients from a distinct geographic region (southern Alberta). The type and location of NHL as well as how it affected the survival of these patients was examined. PATIENTS AND METHODS: The Southern Alberta HIV Clinic in Calgary serves all of southern Alberta, which has an estimated population of one million. The clinic has provided primary care for 1086 patients from January 1983 to August 1995. Data were obtained by reviewing the clinic's database and patients' charts. RESULTS: Over a 12-year period, 39 cases of NHL were diagnosed in a group of 1086 HIV-infected patients. Presentation of NHL was at an extranodal site in all but four cases, with the most common sites being the bowel and central nervous system. The mean CD4 count on presentation with NHL was 143.4±37.4×10 6 /L (range 1 to 1219×10 6 /L). Mean survival was 1.25±0.25 years with a range from 0 (diagnosed on autopsy) to 6.45 years. Patients with a CD4 count of less than 200×10 6 /L and/or diagnosed with an AIDS-defining illness before development of NHL had significantly reduced survival (0.85 years versus 2.48 years, P<0.02 and 0.57 years versus 2.09 years, P<0.001, respectively). Patients who presented with NHL involving either nodes alone or central nervous system had significantly decreased survival (0.28 years and 0.29 years, respectively, P<0.05). Patients with NHL involving the gastrointestinal tract had a longer mean survival than those with NHL elsewhere (P<0.05). All but seven cases received therapy for NHL including chemotherapy, radiotherapy, surgery or combined therapy. Fifteen patients (47% of treated) achieved a complete response that led to improved survival (P<0.01). Patients tolerated surgery, chemotherapy and radiotherapy well and no deaths were due to NHL therapy. CONCLUSIONS: These data suggest that development of NHL in HIV is associated with reduced survival, and that survival is predominantly determined by CD4 count and site of involvement at the time of diagnosis of NHL.